2013
DOI: 10.1200/jco.2012.43.6097
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of RTOG 91-11: A Comparison of Three Nonsurgical Treatment Strategies to Preserve the Larynx in Patients With Locally Advanced Larynx Cancer

Abstract: A B S T R A C T PurposeTo report the long-term results of the Intergroup Radiation Therapy Oncology Group 91-11 study evaluating the contribution of chemotherapy added to radiation therapy (RT) for larynx preservation. Patients and MethodsPatients with stage III or IV glottic or supraglottic squamous cell cancer were randomly assigned to induction cisplatin/fluorouracil (PF) followed by RT (control arm), concomitant cisplatin/RT, or RT alone. The composite end point of laryngectomy-free survival (LFS) was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
930
7
27

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,092 publications
(1,031 citation statements)
references
References 18 publications
26
930
7
27
Order By: Relevance
“…The incidence rates of 10-year cumulative grade 3-4 side effects were also determined for patients receiving CT+RT (31%), concomitant CRT (33%), and RT (38%) protocols. [41] In this study, the incidence of side effects including mucositis, nausea-vomiting, weight loss, neutropenia, and anemia was higher in patients who received CRT rather than RT. The incidence of xerostomia was similar in patients who received RT or CRT.…”
Section: Journal Of Medical Updatesmentioning
confidence: 84%
“…The incidence rates of 10-year cumulative grade 3-4 side effects were also determined for patients receiving CT+RT (31%), concomitant CRT (33%), and RT (38%) protocols. [41] In this study, the incidence of side effects including mucositis, nausea-vomiting, weight loss, neutropenia, and anemia was higher in patients who received CRT rather than RT. The incidence of xerostomia was similar in patients who received RT or CRT.…”
Section: Journal Of Medical Updatesmentioning
confidence: 84%
“…Chemo-radiotherapy (CRT) has increased the curability of locally advanced head and neck cancer patients (HNCPs) [1] and has allowed organ and function preservation in laryngeal and hypo-pharyngeal cancer patients [2]. However, competing causes of mortality (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, more similar to what we currently understand as larynx preservation. 85 A subsequent meta-analysis for locally advanced larynx cancer found that adding CT concomitant ÃÃ T1 and high-volume T4 were excluded: invasion >1 cm into de base of tongue or penetration through caRTilage.…”
Section: Early Stage Disease (Stages I and Ii)mentioning
confidence: 99%